Comparative Study of Ultrasound vs. MRI in Diagnosing Pediatric Hip Dysplasia - Nayyer, Zain; Ihsan, Hafsa; Farid, Muhammad Imran; Ramachandran, Vignesh; Raza, Ali; Mahar, Sijad Ahmed; Raza, Tauseef (Journal of Neonatal Surgery, 2025)
Background: To compare the diagnostic accuracy of ultrasound and MRI in detecting DDH in pediatric patients, with an emphasis on imaging utility across different age groups and clinical scenarios. Methods: This prospective comparative study was conducted on 69 children with suspected DDH from June 2022 to May 2023 at Pediatrics Department Frontier Corps Teaching Hospital Peshawar. All patients underwent ultrasound using the Graf method. MRI was performed in selected cases with inconclusive ultrasound findings or older age. Diagnostic findings, sensitivity, specificity, inter-modality agreement, and impact on treatment planning were analyzed. Results: MRI demonstrated higher sensitivity (94.1%) and specificity (91.6%) compared to ultrasound (85.2% and 76.9%, respectively) with a statistically significant difference (p = 0.031). Complete agreement between the two modalities was observed in 73.9% of cases (Cohen’s Kappa = 0.67, p = 0.004). MRI altered the clinical management plan in 24.6% of cases compared to 11.6% with ultrasound (p = 0.046), though sedation was required in 88.4% of MRI procedures. Conclusion: While ultrasound remains the first-line imaging tool for early DDH diagnosis, MRI provides superior detail and is particularly useful in older children or complex cases. A combined imaging approach enhances diagnostic precision and supports better treatment planning..